Students' Perception of Case‐Based Continuous Assessment and Multiple‐Choice Assessment in a Small Animal Surgery Course for Veterinary Medical Students. Issue 4 (11th March 2014) - Sample, Susannah J.; Bleedorn, Jason A.; Schaefer, Susan L.; Mikla, Amy; Olsen, Christopher W.; Muir, Peter
<x xml:space="preserve">Abstract</x> Objective To determine the relationship between students' perceptions of 2 assessment methods and academic performance. Study Design A 2‐year prospective survey study in a 4‐year Doctor of Veterinary Medicine (DVM) curriculum. Sample Population Year 3 DVM students (n = 44). Methods An assessment of learning gain questionnaire was used to investigate students' perceptions regarding multiple‐choice examination (MCE) versus take‐home case‐based continuous assessment (CA) in a 3rd year small animal surgery lecture course. Academic performance and student assessment of learning gain in the 2 course components were compared. Relationships between student perceptions and academic performance were examined. A follow‐up survey was conducted during clinical rotations in 4th year to determine change in student perceptions over time. Results Academic performance in 3rd year was significantly enhanced by use of CA, particularly for students with weaker grades. Academic performance in 4th year clinical rotations was not closely related to 3rd year performance. Many students preferred an instructional approach with provision of comprehensive notes and assessment with multiple‐choice questions based on the notes. However, students recognized that feedback on work submitted for CA grading significantly facilitated learning. Student assessment of learning gain was correlated with academic performance in the 3rd year course component examined by CA, but not the component assessed using MCE. Conclusion Our data suggest that perceptions of learning gain, academic accomplishment, and clinical performance in 4th year are weakly correlated. Teachers should better explain to veterinary students that learning to be a clinician is more than replication of knowledge.